Influence of Family Structures on Students’ Progression in Public Secondary Schools in Ndhiwa Sub-County, Homabay County, Kenya - Owuor, Emmanuel; Ochieng, Pamela; Kirimi, Josephine (African Journal of Education and Practice, 2023)
Purpose: Students' progression in secondary schools is important in the realization of educational objectives. However, in Ndhiwa Sub-county, students' progression rates has been low in many public secondary schools. Many students drop out of secondary schools just a few years after enrollment. Thus, the purpose of this was to study to examine how family structures influence students' progression in public secondary schools in Ndhiwa Sub-county, Homabay County, Kenya. Methodology: This research adopted mixed methodology and applied concurrent triangulation research design. Target population was 1263 respondents which comprised 65 principals, 678 secondary school teachers and 520 parents' representatives from which 305 respondents were sampled using Yamane's Formula. Stratified sampling was applied to create five strata based on the number of zones in Ndhiwa Sub-county. From each zone, five principals and five parents' representatives were sampled purposively. However, from each zone, simple random sampling was applied to select 51 teachers. This procedure realized a sample size of 25 principals, 25 parents' representatives and 255 teachers. Qualitative data were analyzed thematically based on the objectives and presented in narrative forms. Quantitative data were analyzed using descriptive statistics such as frequencies and percentages and inferentially using multiple linear regression model in Statistical Package for Social Sciences (SPSS Version 23) and presented using tables. Findings: The study established that students' progression has been low with many students who get enrolled in Form I not able to complete their secondary education. This is attributed to large family sizes and family structures. Unique Contribution to Theory, Practice and Policy: As a practice, parents should plan their families and bring forth families they can comfortably take care of such that the meagre amount of financial resources available can cater for the education. As a policy, the Ministry of Health and the Division of National Family Planning should continue with their efforts to teach people on the essence of bring forth families they can manage. The study's unique contribution is that it will reinforce an understanding of how specific aspects of each family structure influence of students' progression in public secondary schools.